Visualization of the air flow behind the automotive benchmark vent - Pech, Ondřej; Jedelský, Jan; Caletka, Petr; Jícha, Miroslav (EDP Sciences, 2015)
Passenger comfort in cars depends on appropriate function of the cabin HVAC system. A great attention is therefore paid to the effective function of automotive vents and proper formation of the flow behind the ventilation outlet. The article deals with the visualization of air flow from the automotive benchmark vent. The visualization was made for two different shapes of the inlet channel connected to the benchmark vent. The smoke visualization with the laser knife was used. The influence of the shape of the inlet channel to the airflow direction, its enlargement and position of air flow axis were investigated.

Passenger comfort in cars depends on appropriate function of the cabin HVAC system. A great attention is therefore paid to the effective function of automotive vents and proper formation of the flow behind the ventilation outlet. The article deals with the visualization of air flow from the automotive benchmark vent. The visualization was made for two different shapes of the inlet channel connected to the benchmark vent. The smoke visualization with the laser knife was used. The influence of the shape of the inlet channel to the airflow direction, its enlargement and position of air flow axis were investigated.
Visualization of the air flow behind the automotive benchmark vent
Keywords: Car vent; smoke visualization; Car vent; smoke visualization